2014
DOI: 10.15669/pnst.4.565
|View full text |Cite
|
Sign up to set email alerts
|

A tangible augmented reality system to support comprehension of radiation shielding

Abstract: A tangible augmented reality (AR) system was developed to visualize electromagnetic cascades through solid materials. 3-D cascade images calculated by the EGS4 simulation software are overlaid on a USB camera image almost in real time. Learners can observe electromagnetic cascades while handling blocks of real shielding materials. This system was demonstrated at a public science event. By way of a questionnaire survey, it appeared that it was the first time to hear about electromagnetic cascades for about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…VR provides users with an internal virtual 3D model and builds a virtual world that looks real to the user's eyes [7]. Earlier studies have reported radiation protection education using AR [8][9][10]. One of the studies involved the use of AR markers to display the AR electromagnetic cascade [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VR provides users with an internal virtual 3D model and builds a virtual world that looks real to the user's eyes [7]. Earlier studies have reported radiation protection education using AR [8][9][10]. One of the studies involved the use of AR markers to display the AR electromagnetic cascade [8].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have reported radiation protection education using AR [8][9][10]. One of the studies involved the use of AR markers to display the AR electromagnetic cascade [8]. Visualisation of the invisible electromagnetic cascade using AR improves user understanding.…”
Section: Introductionmentioning
confidence: 99%